EFIKASI DIRI GURU DALAM IMPLEMENTASI PENDIDIKAN INKLUSIF BERBASIS NILAI-NILAI ISLAM: STUDI KASUS DI SDIT PADANG ISLAMIC SCHOOL - Firsty Sofila; Anita Ulpa; Rahmatul Husna; Adellar Prasetya; Nia Ikhtanova; Roza Naulia Rosdianti; Weni Yulastri (STKIP Subang, 2025)
This study explores teacher self-efficacy in implementing Islamic value-based inclusive education at SDIT Padang Islamic School. The research addresses the critical gap in understanding how teachers' confidence influences their ability to manage diverse learning needs within an Islamic educational framework. Using a qualitative case study approach, data were collected through in-depth interviews with six teachers, participatory classroom observations, and an adapted Teacher Efficacy for Inclusive Practices (TEIP) scale contextualized with Islamic values. Triangulation of data sources revealed that teachers' self-efficacy manifested across Bandura's three dimensions: magnitude (handling various difficulty levels), generality (consistency across different subjects), and strength (persistence through challenges). Islamic values such as patience (sabar), sincerity (ikhlas), and compassion significantly reinforced teachers' self-efficacy, transforming pedagogical challenges into spiritual responsibilities. The findings demonstrate that faith-based contextualization enhances teacher resilience and commitment to inclusive practices. This research contributes to understanding how religious values can be integrated into teacher preparation programs for inclusive education, particularly in faith-based school settings. The study recommends strengthening professional development that incorporates spiritual dimensions to build sustainable teacher self-efficacy in inclusive classrooms.